A 27.5-My underlying periodicity detected in extinction episodes of non-marine tetrapods. (2nd November 2021) - Rampino, Michael R.; Caldeira, Ken; Zhu, Yuhong
ABSTRACT: Non-marine tetrapods (amphibians, reptiles, birds and mammals) have apparently experienced at least 10 distinct episodes of intensified extinctions over the past 300 My. Eight of these ten non-marine extinction events are concurrent with known marine-extinction episodes, which previously yielded evidence for an underlying period of ~26.4 to 27.3 My. We performed circular spectral analysis and Fourier transform analysis of the ages of the ten recognised tetrapod-extinction events, and detected a statistically significant (99% confidence) underlying periodicity of ~27.5 My. We also find that the eight coeval non-marine/marine-extinction pulses all occurred at the times of eruptions of Large Igneous Provinces (LIPs) (continental flood-basalts and oceanic plateaus), with potentially severe environmental effects. Three of these co-extinction episodes are further correlated with the ages of the three largest (≥100-km diameter) impact craters of the last 260 My, which are also apparently capable of causing extinction events. These findings suggest that global cataclysmal events with an underlying periodicity of ~27.5 My were the cause of the coordinated periodic extinction episodes of non-marine tetrapods and marine organisms.